The relations between innovation and internationalization, and between innovation and business performance: evidence from companies operating in Brazil - Yokomizo, Cesar Akira (2014)
Innovation and internationalization are quite often regarded as important strategies for companies to grow and succeed in the fast pacing market battlefield. Literature has deeply investigated these subjects, separately and together. However, papers on the relations of innovation capability and internationalization degree are still scarce and therefore, under researched. Moreover, although studies on the relations of the innovation capability of a company and business performance pop up quite frequently, they still lack conclusiveness. In order to deepen the understanding on those relations and unveil practical recommendations for managers, this study aimed at describing (1) the relations between innovation capability and internationalization degree and (2) the relations between innovation capability and business performance of companies operating in Brazil. Literature review encompasses concepts on innovation drivers, internationalization, and business performance as well as the relations of (1) innovation and internationalization, and (2) innovation and business performance. As innovation capability is not directly measureable, the conceptual model included a proposal of a construct of innovation capability as a weighted contribution of a set of innovation drivers. The conceptual model provided the foundations for the questionnaire and therefore, the whole field research, which included the delivery of questionnaires to students of graduate programs of three Business schools in Brazil. 528 questionnaires were filled out and they represented 386 different companies. Methodological procedures included a quantitative analysis that encompassed (1) descriptive statistics for demographics, (2) the non-parametric Wilcoxon test for mean comparison, (3) exploratory factor analysis for variable reduction, (3) cluster analysis to identify the association of importance and practice of drivers, and (4) multiple linear regression to identify descriptors of internationalization degree and business performance. Idea generation, people, leadership, and intellectual capital are considered the most important innovation drivers as opposed to funding and portfolio management. Regarding practice, although there was no evidence to distinguish most practiced drivers, structure, time, and reward system were considered the less practiced. When considering importance and practice at the same time, five clusters of drivers were depicted: (1) the most practiced, (2) the most important, (3) the least important, (4) the least practiced, and (5) not the most, not the least. Although drivers of cluster (2) are considered the most important, they are not the most practiced. As a result, in general terms, drivers pertaining to this cluster-- people, intellectual capital, generation, conversion, and leadership--should be prioritized while implementing innovation initiatives. Next, while identifying descriptors, funding and diffusion drivers explain 10.6% and innovation capability explains 6.8% of internationalization degree. Findings on the identification of descriptors of business performance are more promising: diffusion, values, strategic alliances, and technologies drivers explain 41.8% of the business performance variability while innovation capability explains 28.1%. Although literature has highlighted the importance of all innovation drivers, the results of this study provide managers with a prioritization when implementing innovation initiatives within their companies, depending on whatever internationalization or business performance output are pursued.